Effect of Dietary Supplementation of Spirulina Platensis and Carrot Meal to Enhance Color Brightness of Oranda Goldfish (Carassius Auratus) - Yuli Andriani; Alan Alamsyah; Walim Lili (JURNAL PERIKANAN DAN KELAUTAN, 2018)
Goldfish is one of the most famous ornamental fish because of body shape and the color which is interesting to culture. The purpose of this experiment is to find the effect of Spirulina platensis and carrot meal was added into feed to increase the red color of koki goldfish. The experiment used Completely Randomized Design with six treatments and three replication. The treatments is 8% Spirulina meal, 8% carrot meal, 0% spirulina meal + carrot meal, 2%+6%, 4%+4%, and 6%+2%. The parameters that observed is color intensity, absolute weight growth, and water quality. The results showed that supplementation of combination 4% spirulina meal and 4% carrot meal gave the best increase in red color on body of koki goldfish with average score 5.93, but no significant effect on growth of goldfish with average growth is 3.55 ± 0.06 gram. Water quality during the research is still in optimal condition and did not affect the enhancement color in goldfish.